Psychometric evaluation of the Turkish version of the Beverage Intake Questionnaire-15 - Gencalp, Cansu; Baris, Olcay; Ones, Ece; Sipahi, Simge; Kahriman, Meryem; Bicer, Nihan Cakir; Yilmaz, Salim; Bas, Murat (Frontiers in Nutrition, 2026)
Background/objectivesOverweight and obesity remain major unresolved public health issues. One contributing factor to the increasing prevalence of obesity is the rising consumption of sugar-sweetened beverages (SSBs), which are a key source of added sugars and excess energy in the diet. Therefore, accurate assessment of beverage intake has become increasingly important for both research and public health interventions. This study aimed to evaluate the validity and reliability of the Turkish version of the Beverage Intake Questionnaire-15 (BEVQ-15) in adults.MethodsA total of 141 adults aged 18–65 years who applied to a private nutrition clinic were included. Data were collected at three time points (T1, T2, T3) through face-to-face interviews. At each time point, participants completed the BEVQ-15 and a 3-day food record. Validity and reliability were evaluated using Spearman correlations, intraclass correlation coefficients, Kendall’s W, and Bland–Altman analyses.ResultsSpearman correlations between BEVQ-15 and food records ranged from 0.26 to 0.96 across beverage categories, with the majority of categories demonstrating correlations of 0.50 or higher. Test–retest reliability was excellent for water (ICC = 0.94), moderate for diet beverages (ICC = 0.70), and total SSBs (ICC = 0.65). Bland–Altman analysis showed that 87% of beverage categories achieved ≥95% agreement within the limits of agreement.ConclusionThese findings indicate that the Turkish version of the BEVQ-15 is a valid and reliable instrument for assessing beverage consumption among adults.